A Secure Framework based On Hybrid Cryptographic Scheme and Trusted Routing to Enhance the QoS of a WSN - Sirajuddin, Mohammad; Ravela, Chittibabu; Rama Krishna, S.; Ahamed, Shaik Khaleel; Basha, S. Karimulla; Jubair Basha, N. Md. (Engineering, Technology & Applied Science Research, 2024)
Achieving Quality of Service (QoS) in Wireless Sensor Networks (WSNs) is challenging, due to their dynamic nature, and many parameters must be taken into account. The main objective of this work is to propose a hybrid cryptographic system with trust-based routing to improve the QoS. This study considers ways to improve QoS while maintaining security. To enhance the performance of the WSN, a framework that uses a hybrid cryptographic system based on a logistic map and the trust-based routing protocol CTBSR that can recognize and counteract a variety of security threats is presented. The findings of this study support the claim that the proposed framework ensures better security than the existing approaches in terms of confidentiality, integrity, and authentication. The performance of the framework introduced is evaluated by employing the NS2 simulator.